Ganglio Centinela:en Cáncer de Vulva - Mamani, Marta; Valfré, Roberto; Mariconde, José María; Castellani, Enrique; Garello, Néstor César (Federación Argentina de Sociedades de Ginecología y Obstetricia (FASGO), 2020)
1 p.